2016
DOI: 10.1111/ajd.12551
|View full text |Cite
|
Sign up to set email alerts
|

Granular parakeratosis induced by benzalkonium chloride exposure from laundry rinse aids

Abstract: Benzalkonium chloride is a quaternary ammonium cationic detergent present in a number of household products, which can act as a major skin irritant. We present the case of six children who developed granular parakeratosis after exposure to benzalkonium chloride in laundry rinse aids, presenting as a brightly erythematous, tender but minimally pruritic, intertriginous eruption followed by superficial desquamation. The eruptions resolved over 3-4 weeks after cessation of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 5 publications
0
36
1
Order By: Relevance
“…Future studies will need to explore how changing lifestyles, environments and even medical practices including use of cleansing agents and preservatives in topical preparations impact on the microbial communities on the human body. Some cases of granular parakeratosis have been associated with use of benzalkonium chloride . We believe that it is not a primary contact dermatitis but an alteration of the surface microbiome that leads to hyperkeratotic flexural erythema clinical picture.…”
Section: Discussionmentioning
confidence: 88%
“…Future studies will need to explore how changing lifestyles, environments and even medical practices including use of cleansing agents and preservatives in topical preparations impact on the microbial communities on the human body. Some cases of granular parakeratosis have been associated with use of benzalkonium chloride . We believe that it is not a primary contact dermatitis but an alteration of the surface microbiome that leads to hyperkeratotic flexural erythema clinical picture.…”
Section: Discussionmentioning
confidence: 88%
“…Although well documented as a skin irritant, benzalkonium chloride is commonly used in hand sanitisers and household cleaning products 7,8 and has been associated with development of granular parakeratosis in the paediatric population. 9 While it is included as a contact allergen on the Australian Baseline Series (ABS), several reports 7,8 including one comparative study using an atopic mice model have identified benzalkonium chloride as a significant irritant that can cause eczematous dermatoses to a greater degree than other commonly used antiseptic agents such as povidone-iodine, ethanol and chlorhexidine gluconate. 8 In a recent case series by Robinson and colleagues 9 six children presented with granular parakeratosis secondary to benzalkonium chloride exposure following the use of antiseptic laundry rinse by Dettol (Reckitt Benckiser, Beijing, China) or Canesten (Bayer Australia, Sydney, NSW, Australia).…”
Section: Research Lettermentioning
confidence: 99%
“…It was first described in 1991 with a case series of four patients with granular parakeratosis involving the axilla 2. Since the initial case series, additional cases of granular parakeratosis have been described,3–8 including several with involvement of multiple intertriginous sites 9 10…”
Section: Descriptionmentioning
confidence: 99%